2020
DOI: 10.1080/07315724.2020.1774441
|View full text |Cite
|
Sign up to set email alerts
|

Beetroot (Beta Vulgaris L.) Extract Acutely Improves Heart Rate Variability Recovery Following Strength Exercise: A Randomized, Double-Blind, Placebo-Controlled Crossover Trial-Pilot Study

Abstract: Objective: We assessed the acute effect of beetroot extract intake on cardiovascular and autonomic recovery subsequent to strength exercise. Methods: This is a crossover, randomized, double-blind and placebo-controlled trial. We assessed 16 subjects but only 12 healthy male adults completed the two protocols in two randomized days: Beetroot extract (600 mg in capsule) and placebo (600 mg starch in capsule). Beetroot extract or placebo was ingested, the subjects endured 120 minutes seated at rest, followed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 40 publications
2
16
0
2
Order By: Relevance
“…Recently, Benjamin et al. 21 showed that beetroot extract can acutely improve both cardiovascular and autonomic recovery after resistance exercise in healthy young adults. In this study, the HRV index (in time and non-linear domains) responses after exercise were similar to ours, showing that the exercise improved post-exercise HRV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Benjamin et al. 21 showed that beetroot extract can acutely improve both cardiovascular and autonomic recovery after resistance exercise in healthy young adults. In this study, the HRV index (in time and non-linear domains) responses after exercise were similar to ours, showing that the exercise improved post-exercise HRV.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Benjamin et al. 21 also showed that beetroot extract intake acutely improved cardiovascular and autonomic recovery after exercise in young healthy male adults.…”
Section: Introductionmentioning
confidence: 96%
“…Numerous studies have xated on investigating whether nutritional interventions (e.g., energy drinks, caffeine) [11][12][13][14] can induce a delay in the recovery of HR and HRV and so increase cardiovascular risk. Others researches pursues the identi cation of compounds that optimize these parameters and minimize the cardiac stress produced by physical exercise 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Benjamin et al 21 showed that beetroot extract can acutely improve both cardiovascular and autonomic recovery after resistance exercise in healthy young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions were observed by Bond et al 20 in African descent women in which the intake of BJ reduced BP and improved HRV. More recently, Benjamin et al 21 also showed that beetroot extract intake acutely improved cardiovascular and autonomic recovery after exercise in young healthy male adults.…”
Section: Introductionmentioning
confidence: 96%